Los bonos por productividad y su influencia en los costos laborales de una empresa agraria de la provincia de Trujillo en el año 2016 - Cava Quezada, Arthur Clark (2017)
The present investigation was carried out with the purpose of determining the influence of productivity bonuses on the labor costs of an agrarian enterprise in the province of Trujillo in 2016. As hypothesis it was considered: Productivity bonuses positively influence the labor costs of an agrarian enterprise in 2016. We used non-experimental descriptive research design, using quantitative historical information provided by the research company. The variables of study were, the productivity bonds which is a remunerative payment delivered to the worker in relation to the number of jars harvested during his working day; And the labor costs that is the result of all the remunerative concepts that are paid to the worker in relation to his working hours. The research concludes that the influence of productivity bonuses on labor costs is positive, since with the implementation of the bonus the hiring of more labor was reduced, leading to the reduction of labor costs. It is recommended to develop an intensive training program by the most experienced and efficient staff in the harvest for the incoming personnel that initiates harvesting work as well as to perform a non-monetary recognition as diplomas to the best harvester of the campaign and / or the best harvester group Of the campaign to achieve an intangible value that also serves as a motivation for the workers. As a measure of control, it is recommended to follow up on a monthly basis the variations between the use of productivity bonuses and labor costs.